Toxicological Assessments of a Proprietary Blend of Punica granatum Fruit Rind and Theobroma cacao Seed Extracts: Acute, Subchronic, and Genetic Toxicity Studies. (6th May 2022) - Madireddy, Ravi Kumar; Alluri, Krishnaraju Venkata; Somepalli, Venkateswarlu; Golakoti, Trimurtulu; Sengupta, Krishanu
Abstract : LN18178 (Tesnor ® ) is a standardized, proprietary composition of aqueous ethanol extracts of Punica granatum fruit rind and Theobroma cacao seeds. The present study demonstrates a broad-spectrum toxicological evaluation of LN18178 utilizing in vitro and in vivo preclinical models following the Organization for Economic Cooperation and Development (OECD) guidelines for testing chemicals. Wistar rats did not show any clinical signs of toxicity and morbidity in acute oral and dermal toxicity tests with the median lethal dose (LD50 ) values of at least 5000 mg/kg and 2000 mg/kg body weight, respectively. LN18178 was nonirritating to the skin and eyes of the treated rabbits. In a ninety-day subchronic repeated oral dose toxicity study, the LN18178-treated Wistar rats did not show dose-related signs of toxicity on their body weight, food consumption, organ weights, hematology, and clinical chemistry parameters. The estimated no-observed-adverse-effect level (NOAEL) of LN18178 in male and female rats was 2500 mg/kg body weight. The observations from the bacterial reverse mutation test, in vitro chromosomal aberration assay, micronucleus assay in mouse bone marrow erythrocytes, and in vitro mouse lymphoma TK +/− gene mutation assay suggest that LN18178 is neither mutagenic nor clastogenic. In summary, the present study demonstrates that oral consumption of the herbal blend LN18178 does not show signs of toxicity; also it does not elicit genetic toxicity in the standard preclinical models.